Bhaktapur Urban Flood related Disaster Risk and Strategy after 2018 - Bhatta, Bishnu Prasad; Pandey, Ramesh Kumar (Journal of APF Command and Staff College, 2020)
The urbanization led urban flooding phenomenon of the Hanumante River over the last few decades is the subject of this article. The river flows in the middle of the Bhaktapur District and connects with all municipalities. Its catchment area is 97km². The data offers deeper insights into sources, causes and impacts of the flood. All stakeholders are aware of their roles and responsibilities during the disaster. However, affected people have limited understanding and knowledge about the flood and remain in fear of another flood every year. The major cause of floods in the district is incessant rain and urbanization leads to the inundation of various low lying areas. However, increased urbanization, lack of proper planning and encroachment of river are supplementary causes of floods. Floods can be predicted and mitigated with appropriate information, tools and techniques by responsible agencies. Often disasters are a failure of responsible agencies to act timely and to understand the environmental changes and the urban push. Inundation is becoming a common phenomenon for urban people in most cities.